2002
DOI: 10.1016/s0006-3495(02)75591-4
|View full text |Cite
|
Sign up to set email alerts
|

SANS Study on the Effect of Lanthanide Ions and Charged Lipids on the Morphology of Phospholipid Mixtures

Abstract: The structural phase behavior of phospholipid mixtures consisting of short-chain (dihexanoyl phosphatidylcholine) and long-chain lipids (dimyristoyl phosphatidylcholine and dimyristoyl phosphatidylglycerol), with and without lanthanide ions was investigated by small-angle neutron scattering (SANS). SANS profiles were obtained from 10 degrees C to 55 degrees C using lipid concentrations ranging from 0.0025 g/ml to 0.25 g/ml. The results reveal a wealth of distinct morphologies, including lamellae, multi-lamella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
199
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(230 citation statements)
references
References 37 publications
(41 reference statements)
29
199
2
Order By: Relevance
“…Beyond this range, DMPC/DHPC/DMPG mixtures form discoidal bicelles or MLV. [23][24][25][26] A structural phase diagram of lipid mixtures in the dilute regime (C lp < 1.00 wt %) is presented. It is found that under numerous experimental conditions the ULV size is insensitive to both C lp and C s .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this range, DMPC/DHPC/DMPG mixtures form discoidal bicelles or MLV. [23][24][25][26] A structural phase diagram of lipid mixtures in the dilute regime (C lp < 1.00 wt %) is presented. It is found that under numerous experimental conditions the ULV size is insensitive to both C lp and C s .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies examining the effect of charge on ULV formation have demonstrated that insufficient or excess charge densities can inhibit their formation and instead, result in the formation of MLVs (insufficient charge) or bicelles (excess charge). 21 Here we focused on a narrower range of charge densities (i.e., [DMPG]/[DMPC] ) 0.3, 0.8, and 1.5%) in order to gain a more detailed understanding of the system studied, as summarized in Figure 8. 21 In the case where there is an insufficient amount of charge to cause bilayers to unbind, MLVs are the stable morphology.…”
Section: Discussionmentioning
confidence: 99%
“…21 Here we focused on a narrower range of charge densities (i.e., [DMPG]/[DMPC] ) 0.3, 0.8, and 1.5%) in order to gain a more detailed understanding of the system studied, as summarized in Figure 8. 21 In the case where there is an insufficient amount of charge to cause bilayers to unbind, MLVs are the stable morphology. 32 The present system forms an opaque liquid indicative of MLVs for all temperatures studied, a result confirmed by SANS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations